2022
DOI: 10.3389/fgene.2022.1033214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping of esophageal squamous cell carcinoma by large-scale transcriptional profiling: Characterization, therapeutic targets, and prognostic value

Abstract: The tumor heterogeneity of the transcriptional profiles is independent of genetic variation. Several studies have successfully identified esophageal squamous cell carcinoma (ESCC) subtypes based on the somatic mutation profile and copy number variations on the genome. However, transcriptome-based classification is limited. In this study, we classified 141 patients with ESCC into three subtypes (Subtype 1, Subtype 2, and Subtype 3) via tumor sample gene expression profiling. Differential gene expression (DGE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…Functional enrichment analysis showed that Kif14 was mainly enriched in 'macroautophagy' and 'pyrimidine metabolism'. In addition, Kif14 was also active in signaling pathways such as Wnt signaling 54 , 55 , Hedgehog signaling 56 , 57 , and PI3K/Akt signaling 58 . To date, there have been no studies on the direct involvement of the above biomarkers in the osteogenic differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Functional enrichment analysis showed that Kif14 was mainly enriched in 'macroautophagy' and 'pyrimidine metabolism'. In addition, Kif14 was also active in signaling pathways such as Wnt signaling 54 , 55 , Hedgehog signaling 56 , 57 , and PI3K/Akt signaling 58 . To date, there have been no studies on the direct involvement of the above biomarkers in the osteogenic differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the advanced or metastatic nature of many gastroesophageal cases at diagnosis, the overall 5-year survival rate remains less than 20% in developing countries [ 2 , 3 ]. The main factors affecting gastroesophageal cancers prognosis include tumor staging and grading, treatment method, living condition, and genetic marker [ 4 , 5 ]. However, as a transitional region tumor from esophageal squamous epithelium to the gastric adenoid epithelium, it is possible that the oncological principles for esophageal and gastric cancer are not directly applicable to junctional cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%